IMPROVEMENT OF TECHNOLOGIES OF THE METAL THERMAL PROCESSING ON THE BASIS OF THE INDUCTION HEATING PROCESSING. Message 1. Analysis of the perspective areas of induction heating usage - I. A. Trusova; D. V. Mendelev; P. E. Ratnikov (Литьë и металлургия)
Promising directions of induction heating are analyzed.